A Study the Performance of Wireless Mobile Ad Hoc Networks Routing Protocols: Investigating the Performance of Wireless Mobile Ad Hoc Networks Routing Protocols (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The explosive reputation of Ad Hoc Network and the availability of wide variety of computing andcommunicating devices over the past few years lead to superior degree of demand for MANET in computerand communication field. It has been found that MANET has been under stable resource of interest amongthe researchers for the last two decades. Several researches have been carried out to improve theperformance, but there are still some notable improvements to be performed in Mobile Ad Hoc Network onvarious aspects. MANET is a collection of arbitrarily movable mobile nodes that build a temporaryinfrastructure less network without any support from the centralized controller. The mobile nodes canmove around but they are still remaining connected with the rest of the world. The study helps tounderstand the research on the performance of the MANET.